KARAKTERISTIK APARATUR, LINGKUNGAN ORGANISASI DAN INDIKATOR KINERJA ORGANISASI - Rianto, Tamda (Jurnal Ilmu Administrasi Negara, 2016)
Characteristics Apparatus, Environment Organization and Organizational Performance Indicators. This study aims to determine the effect of the characteristics and environment of the organization to the achievement of performance indicators Riau Forestry Service. In keeping with its focus, this research uses descriptive qualitative methods to describe the state of the subject/object of research based on the facts that appear or as their (fact finding). The informants were employees of the Forestry Service of Riau. Samples were taken using snowball sampling. The data collection is done by observation, interview and documentation techniques. The results showed that the characteristics of the apparatus influential in achieving performance indicators Riau Forestry Service. Paternalistic and organizational culture change and organizational structure of the replacement officials in Riau Forestry Service so quickly affect the achievement of organizational performance indicators Riau Forestry Service.